THE IMPACT OF APPLYING BIG DATA TECHNOLOGY IN DIGITAL BUSINESS MANAGEMENT - Camelia Safitri; Dwi Aris Nurohman; Burhanuddin (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Big data plays a role in controlling the reputation of your online business. The tools in big data can carry out sentiment analysis, so business people will be able to see how much feedback there is about who has given the company a response. The final role is that big data will be able to understand customers well. Big data will be able to find out what customers want and provide the best service to them. Big Data-based implementation involves selecting and using appropriate Big Data technologies and platforms, such as distributed storage and processing systems, advanced data analysis algorithms, data visualization techniques, and machine learning methods. By effectively leveraging big data, companies can improve their understanding of consumers, design more effective marketing strategies, and provide a more personalized shopping experience. By leveraging Big Data technology and infrastructure, organizations can collect, manage and analyze data on a large scale. This enables them to identify new patterns, relationships and insights that support strategic decision making, development of customer understanding and optimization of business processes.